Prevalence and risk factors for epiretinal membrane: the Singapore Epidemiology of Eye Disease study. Issue 3 (24th June 2016) - Cheung, Ning; Tan, Shu-Pei; Lee, Shu Yen; Cheung, Gemmy Chui Ming; Tan, Gavin; Kumar, Neelam; Cheng, Ching-Yu; Wong, Tien Yin
Abstract : Aim: To examine prevalence and risk factors of epiretinal membrane (ERM) in a large, contemporary, multiethnic Asian population. Methods: Combined analysis of three population-based studies of eye diseases, with a total of 9799 Chinese, Malays and Indians residing in the general communities of Singapore. A comprehensive ophthalmic examination, interviews and laboratory blood tests were performed to assess potential risk factors. Digital retinal photographs were used to assess ERM according to a standardised protocol. ERM was classified into cellophane macular reflex (CMR) and/or preretinal macular fibrosis (PMF), and also as primary or secondary (in eyes with other retinal pathology or a history of cataract surgery). Results: The age-standardised and ethnicity-standardised prevalence was 12.1% for any ERM, 6.8% for CMR, 6.7% for PMF and 2.8% for bilateral ERM. ERM prevalence was higher in Chinese (13.0%) compared with Malays (7.9%) or Indians (8.7%). In multivariate analysis, significant factors associated with primary ERM were older age (OR 1.08 per year increase; p<0.01), Chinese ethnicity (OR 1.60 vs Indians; p<0.01; OR 1.39 vs Malays; p<0.01), smoking (OR 0.70; p=0.01), longer axial length (OR 1.07 per mm increase; p=0.03) and cataract (OR 0.64; p<0.01). Significant factors independently associated with secondary ERM were older age (OR 1.05; p<0.01), cataract surgery (OR 10.6; p<0.01) and diabetic retinopathy (OR 2.48; p<0.01). Conclusions: ERM is common in Asians, particularly among Chinese. Older age is the most consistent risk factor for any ERM, and previous cataract surgery and diabetic retinopathy are the strongest risk factors for secondary ERM.